A299 IDENTIFICATION OF PATHOGENIC BACTERIAL STRAINS IN PAEDIATRIC PATIENTS WITH INFLAMMATORY BOWEL DISEASES USING IMMUNOGLOBULIN G AS A MARKER OF VIRULENCE. (1st March 2018) - Alipour, M; Armstrong, H; Valcheva, R S; Zaidi, D; Jovel, J; Lou, Y; Mason, A; Wong, G; Madsen, K; Dieleman, L A; Carroll, M W; Huynh, H Q; et al.
Abstract: Background: Inflammatory bowel diseases (IBD), including Crohn disease (CD) and ulcerative colitis (UC), are a group of chronic and severely debilitating gastrointestinal disorders, with an exacerbated immune response to the gut microbiota. Aims: We hypothesized that pathogenic bacteria are more likely to be bound by immunoglobulin (Ig) G antibodies and identification of these strains could help identify mechanisms of immune activation. Methods: Aspirate washes were obtained from the terminal ileum of pediatric IBD and non-IBD patients during endoscopy. Samples were fixed in paraformaldehyde and stringently washed to separate bacteria. Prior to fluorescence-activated cell sorting (FACS), samples were stained with propidium iodide (PI) and an anti-IgG fluorescent antibody with proper controls to differentiate bacteria bound by IgG (IgG+) from all others (IgG-). Validation in a select set of samples involved image cytometry. DNA was extracted from sorted bacteria using bead beating extraction and phenol/chloroform purification. Analysis of bacterial DNA samples was completed using the Ilumina MiSeq platform for 16S rRNA gene sequencing. Results: Quality of patient bacterial DNA samples was used to identify those suitable to be sequenced resulting in 36 total washes from children without IBD (n=10), and with CD (n=17) or UC (n=9). Firmicutes and Bacteroidetes phyla were most commonly identified; however, no significant differences were found between IBD and non-IBD controls upon examining the composition of the ileal mucosa-associated microbiome. There was a 2 and 1.5 fold increase in the overall ratio of IgG+/IgG- bacteria in CD and UC, respectively. In CD, there was an increase in IgG+/IgG- ratio of both Bacteroidetes and Proteobacteria phyla. In UC this ratio was increased for Actinobacteria. IgG binding favored specific family level strains including Porphyromonadaceae (Bacteroidetes) and Enterobacteriaceae (Proteobacteria) in CD; Barnesiellaceae (Bacteroidetes) and Bifidobacteriaceae (Actinobacteria) in UC; and Clostridiaceae and Veillonellaceae (Firmicutes) in non-IBD, although considerable variation was noted between patients. Conclusions: This study demonstrated selective increase of mucosa associated bacteria bound by IgG in the ileum of pediatric IBD patients compared to non-IBD. Further use of this method in larger cohort studies can identify individual microbes as therapeutic targets facilitating the development of targeted diagnostic and improved therapeutic approaches for IBD. Funding Agencies: CCCCCFC, AIHS